Telehealth based parental support over 6 months improves physical activity and sleep quality in children with autism: a randomized controlled trial - Xin Shen; Xin Shen; Peiying Huang; Peiying Huang; Qian Liu; Qian Liu; Yin Guo; Yin Guo; Lan Zheng; Lan Zheng (Frontiers in Pediatrics, 2024)
PurposeSleep disturbances are prevalent in autistic children. The emergence of telehealth offers new possibilities for remote professional intervention. By combining telehealth with parental support, this study aims to explore a novel family-based model to enhance moderate-to-vigorous physical activity (MVPA) and improve sleep quality in children with autism.MethodsThirty-four autistic children (mean age = 15.7 years) were randomly assigned to either a 6-month intervention group or a control group. Both groups received standard physical education classes at school. The intervention group received additional after-school telehealth support. MVPA and sleep quality were assessed 1 week before the intervention and at the 6-month follow-up.ResultsAfter 6 months, children in the intervention group nearly doubled their daily MVPA compared to the control group (Cohen's d = 8.34, CI95% = 6.17–10.52). Actigraphy-assessed sleep efficiency was notably higher (d = 2.35, CI95% = 1.44–3.26), and there were reductions in wake time (d = 1.65, CI95% = 0.84–2.46), sleep fragmentation (d = 0.80, CI95% = 0.07–1.52), and sleep latency (d = 0.82, CI95% = 0.09–1.54) were all reduced. These improvements in objective sleep metrics were corroborated by subjective assessments using the Sleep Disturbance Scale for Children (d = 0.86, CI95% = 0.13–1.59).ConclusionsTelehealth combined with parental support addresses barriers to enhancing health behaviors at home. This innovative model not only improves after-school MVPA and sleep quality in autistic children but also holds significant potential for benefiting other populations requiring remote support.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT06444659?id=NCT06444659&rank=1 (NCT06444659).